All sequential allotment rules are obviously strategy-proof - R. Pablo Arribillaga; Jordi Massó; Alejandro Neme (Theoretical Economics, 2023)
For division problems with single-peaked preferences, we show that all sequential allotment rules, a large subfamily of strategy-proof and efficient rules, are also obviously strategy-proof. Although obvious strategy-proofness is in general more restrictive than strategy-proofness, this is not the case in this setting.
Keywords: D71; 330; division problems; Obvious strategy-proofness; sequential allotment rules; single-peaked preferences